Challenges facing cancer care and guidance on prioritising its safe delivery: lessons from the COVID-19 pandemic. (2nd June 2022) - Smith, Nikki D; Radhakrishna, Ganesh; Paton, Nina; Hechter, Stephanie; Foulkes, Mark; Mohammed, Mohammed A; Boudioni, Markella
Abstract : The COVID-19 pandemic challenged the NHS to make rapid adjustments to practice to ensure that patients could continue to access vital treatments while reducing the risk of infection. A roundtable discussion was convened, including professionals from cancer care delivery and those working in patient involvement, to discuss experiences during the pandemic and to offer recommendations for the safe transition and implementation of cancer care in the community setting.